Clinical effectiveness of platelets in additive solution treated with two commercial pathogen‐reduction technologies. Issue 5 (24th February 2017) - Rebulla, Paolo; Vaglio, Stefania; Beccaria, Francesco; Bonfichi, Maurizio; Carella, Angelo; Chiurazzi, Federico; Coluzzi, Serelina; Cortelezzi, Agostino; Gandini, Giorgio; Girelli, Gabriella; Graf, Maria; Isernia, Paola; et al.
Abstract : BACKGROUND: Two noninferiority, randomized, controlled trials were conducted in parallel comparing the safety and efficacy of platelets treated with Intercept or Mirasol pathogen‐reduction technologies versus standard platelets. STUDY DESIGN AND METHODS: The primary endpoint was the percentage of hematology patients who developed World Health Organization Grade 2 or greater bleeding. A noninferiority margin of 11% was chosen based on expected Grade 2 or greater bleeding in 20% of controls. The study was closed for financial restrictions before reaching the planned sample size of 828 patients, and an intention‐to‐treat analysis was conducted on 424 evaluable patients. RESULTS: In the Intercept trial (113 treated vs. 115 control patients), the absolute risk difference in Grade 2 or greater bleeding was 6.1%, with an upper one‐sided 97.5% confidence limit of 19.2%. The absolute risk difference in the Mirasol trial (99 treated vs. 97 control patients) was 4.1%, and the upper one‐sided 97.5% confidence limit was 18.4%. Neither absolute risk difference was statistically significant. In both trials, posttransfusion platelet count increments were significantly lower in treated versus control patients. Mean blood component use in treated patients versus controls was 54% higher (95% confidence interval, 36%‐74%; Intercept) and 34% higher (95% confidence interval, 16%‐54%; Mirasol) for platelets and 23% higher (95% confidence interval, 8%‐39%; Intercept) and 32% higher (95% confidence interval, 10%‐57%; Mirasol) for red blood cells. Unexpected reactions and adverse events were not reported. Mortality did not differ significantly between treated and control patients. CONCLUSION: Although conclusions on noninferiority could not be drawn due to low statistical power, the study provides additional information on the safety and efficacy of pathogen‐reduced platelets treated with two commercial pathogen‐reduction technologies.